1981
DOI: 10.1037/0096-1523.7.4.825
|View full text |Cite
|
Sign up to set email alerts
|

Area and contrast effects upon perceptual and imagery acuity.

Abstract: We measured the size of visual fields within which actual and imagined circular patterns could be resolved, as the patterns varied in both area and relative contrast. As pattern area increased, imagery fields increased in size at the same rate as perceptual fields. However, as the relative contrast between parts of the patterns was reduced, perceptual fields diminished in size, while imagery fields did not. For all variations of pattern area and contrast, fields in imagery were roughly the same shape as fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1

Year Published

1982
1982
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 7 publications
1
31
1
Order By: Relevance
“…The substitution of an image for a physical stimulus to create a percept has recently been shown to be a possibility for a variety of phenomena. As examples, such substitution has been reported for perceptual adaptation to displacing prisms (Finke, 1979), letter search and identification (Podgorny & Shepard , 1978), observation of the McCollough effect (Finke & Schmidt , 1977Kunen & May, 1980), perceptual acuity of objects in the peripheral visual field (Finke & Kosslyn, 1980), perception of area and contrast effects (Finke & Kurtzman, 1981), production of the Poggendorff illusion (Goldstein & Weintraub, 1973;Pressey & Wilson, 1974), and creation of the autokinetic effect (Wallace, 1980). Finke (1980) argued that not only can an image substitute for a physical stimulus, but also that the two are equivalent in their effect on perception.…”
mentioning
confidence: 87%
“…The substitution of an image for a physical stimulus to create a percept has recently been shown to be a possibility for a variety of phenomena. As examples, such substitution has been reported for perceptual adaptation to displacing prisms (Finke, 1979), letter search and identification (Podgorny & Shepard , 1978), observation of the McCollough effect (Finke & Schmidt , 1977Kunen & May, 1980), perceptual acuity of objects in the peripheral visual field (Finke & Kosslyn, 1980), perception of area and contrast effects (Finke & Kurtzman, 1981), production of the Poggendorff illusion (Goldstein & Weintraub, 1973;Pressey & Wilson, 1974), and creation of the autokinetic effect (Wallace, 1980). Finke (1980) argued that not only can an image substitute for a physical stimulus, but also that the two are equivalent in their effect on perception.…”
mentioning
confidence: 87%
“…Similarities between processing of perceptually available objects and processing of memories of the same objects are commonly taken as evidence that the purely mental processing uses representations that are close to perception (Banks, 1981;Finke, 1980;Finke & Kurtzman, 1981;Shepard, 1978;Shepard & Podgorny, 1978). Conversely, in cases in which the two sorts of processing give dissimilar results, it should be concluded that the mental processing does not use perceptual representations.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, these subjects imagined that they saw their pointing finger arrive at one side of the target when they pointed at it, in such a way that they imagined making the same average prism-induced errors that subjects in the perceptual feedback condition actually did make and observe. This was done using the following technique: As shown in Figure 5, a set of visual markers was placed to one side of the target, corresponding to the average pointing errors that subjects in the perceptual condition made on their first pointing trial (Y), on Trials 1-5 (1), on Trials 6-10 (2), and on Trials 11-20 (3). The subjects in the imagery condition were instructed, prior to the adaptation procedure, to try to point to where they saw the target, but then to imagine that they saw their pointing finger arrive under each of the markers in that same sequence.…”
Section: Mental Images For Errors Of Movementmentioning
confidence: 99%